Composite sodium ferric phosphate positive electrode material with high compaction density, preparation method of composite sodium ferric phosphate positive electrode material and application of composite sodium ferric phosphate positive electrode material in sodium ion battery
By adding surfactant to the aqueous solution of the positive electrode material of the sodium ion battery, the particle dispersion and uniform composition are achieved, and the problems of complex synthesis and low gram capacity of the existing sodium ion battery positive electrode material are solved, the compaction density and electrochemical performance of the material are improved, and the energy density of the battery is improved.
Patent Information
- Application Number
- CN202411814677.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing sodium ion battery cathode materials such as NaFePO4 and NaFeP2O7 hinder industrialization due to complex synthesis steps and low capacity. Although Na4Fe3(PO4)2P2O7 has a good theoretical capacity, it is difficult to control the heterogeneous phase, resulting in a low actual capacity, which in turn affects the energy density.
By adding appropriate surfactant to the aqueous solution, uniform dispersion of insoluble or insoluble particles is achieved, ensuring the particle consistency and uniform composition of the precursor powder. After heat treatment and powder crushing, a composite sodium iron phosphate positive electrode material with high purity, small particle size and uniform distribution is obtained.
The compaction density of the powder and electrode sheet of composite sodium iron phosphate positive electrode material is improved, the crystal phase purity and electrochemical performance are enhanced, the capacity attenuation is reduced, and the energy density of sodium ion batteries is improved.
Smart Images

Figure CN119637837A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of sodium ion batteries, and in particular to a method for preparing a composite sodium iron phosphate positive electrode material with a high compaction density and a pole piece thereof. Background Art
[0002] Sodium-ion batteries, which are rich in resources and low in cost, are gradually developing and rising in the field of energy storage. The positive electrode materials of sodium-ion batteries mainly include three categories: layered oxides, Prussian blues and polyanion compounds. Compared with layered oxides and Prussian blues, polyanion compounds such as sodium vanadium phosphate, sodium iron sulfate, sodium iron phosphate, etc. have become the superior positive electrode materials of low-cost and high-stability sodium-ion batteries due to their stable structure, fast diffusion of sodium ions and high safety. Among them, vanadium-based phosphate positive electrode materials are difficult to produce and apply on a large scale due to the high price of vanadium sources and strong biological toxicity; sodium iron sulfate, due to its high air sensitivity, faces problems such as low yield and low air stability in commercial development like layered oxides, and is also difficult to produce and apply on a large scale. Based on such problems, in order to maximize the development and utilization of the safety and low-cost advantages of sodium-ion batteries, the development of iron-based phosphate positive electrode materials using the iron ion valence reaction of abundant iron sources will be a new way to commercialize sodium-ion batteries.
[0003] The iron-based phosphate cathode materials that have been developed include: Na4Fe3(PO4)2P2O7, NaFePO4, NaFeP2O7, etc. However, the complex synthesis steps and low capacity of NaFePO4 and NaFeP2O7 have become a major obstacle to industrialization. Na4Fe3(PO4)2P2O7 has become a promising cathode material for sodium-ion batteries due to its good theoretical capacity and simple solid-phase reaction synthesis steps. However, Na4Fe3(PO4)2P2O7 cathode materials face the problems of difficult control of the impurity phase of NaFePO4 and NaFeP2O7, resulting in low actual gram capacity. In the preparation process of the whole battery, it will face low gram capacity under high electrode compaction density, which will further lead to lower energy density. Summary of the invention
[0004] In order to solve the above problems, the present invention can achieve uniform dispersion of insoluble or poorly soluble particles in the solution by adding appropriate surfactants to the aqueous solution before spray granulation, and convert the aqueous solution into a homogeneous mixed solution. It can further ensure that the precursor powder of the aqueous solution after the spray drying process has high particle consistency and uniform particle composition; when the precursor powder is heat treated and crushed, the final product obtained has high purity, and the obtained particles are small in size and highly evenly distributed, which will further lead to the final product having a higher powder compaction density and pole piece compaction density.
[0005] The present invention adopts the following technical solution:
[0006] The present invention provides a method for preparing a composite sodium iron phosphate positive electrode material with a high compaction density, comprising the following steps:
[0007] (1) The sodium source, iron source, phosphorus source, etc. for preparing the composite sodium iron phosphate positive electrode material are measured, mixed and ground according to the chemical formula Na4Fe3(PO4)2P2O7, and a carbon source with a mass percentage of 8% is added to obtain a precursor aqueous solution;
[0008] (2) adding a surfactant to the precursor aqueous solution, grinding and mixing the mixture to obtain a homogeneous precursor aqueous solution;
[0009] (3) drying and granulating the homogeneous precursor aqueous solution by spray drying technology to obtain composite sodium iron phosphate precursor particles;
[0010] (4) subjecting the composite sodium iron phosphate precursor particles to high-temperature heat treatment under the protection of an inert gas to obtain a composite sodium iron phosphate positive electrode material.
[0011] Furthermore, the chemical formula of the composite sodium iron phosphate is Na4Fe3(PO4)2P2O7.
[0012] Furthermore, the mixing ratio of the sodium source, iron source and phosphorus source is 4:3:4.
[0013] Furthermore, the sodium source includes one or more of sodium acetate, sodium oxalate, sodium nitrate, sodium citrate, sodium phosphate, and sodium alginate;
[0014] The iron source includes one or more of ferric phosphate, ferrous oxalate, ferric nitrate and ferric sulfate;
[0015] The phosphorus source includes one or more of sodium dihydrogen phosphate, disodium hydrogen phosphate, phosphoric acid, diammonium dihydrogen phosphate, triammonium phosphate, diammonium hydrogen phosphate, sodium phosphate, etc.;
[0016] The carbon source comprises one or more of citric acid, glucose, sucrose, polyethylene glycol, lignin, nanocellulose and phenolic resin.
[0017] Furthermore, the surfactant includes one or more of fatty alcohol polyoxyethylene ether (A), alkylphenol polyoxyethylene ether (B) and polyoxyethylene alkylphenol ether (C).
[0018] Furthermore, after the surfactant is introduced, its mass proportion in the precursor aqueous solution is 0.2% to 4%.
[0019] Furthermore, the average particle size of the homogeneous precursor aqueous solution is 0.1 μm to 0.7 μm, and the solid content of the homogeneous precursor aqueous solution is 15% to 60%.
[0020] Furthermore, in the step (3), the spray drying technology, wherein the drying temperature is 170°C to 250°C, and the drying atmosphere is one of air, nitrogen, and argon;
[0021] In step (4), the high temperature heat treatment temperature is 400°C to 600°C, the heat treatment time is 3 to 10 hours, the inert gas is one of nitrogen or argon, and the heating rate is 1°C / min to 10°C / min.
[0022] Furthermore, the average particle size of the composite sodium iron phosphate positive electrode material is 300-700 nm; the carbon content is 1.5-2.0%; and the powder compaction density is 2.0-2.65 g / cm 3 .
[0023] The invention also discloses a composite sodium iron phosphate positive electrode material, which is prepared by the composite sodium iron phosphate positive electrode material preparation method.
[0024] The invention also discloses a sodium ion battery positive electrode sheet, which is prepared from the above-mentioned composite sodium iron phosphate positive electrode material.
[0025] The compaction density of the sodium ion battery positive electrode sheet is 1.5 g / cm 3 ~2.6g / cm 3 .
[0026] The invention also discloses a sodium ion battery using the aforementioned sodium ion battery positive electrode sheet.
[0027] The beneficial effects of the present invention include the following:
[0028] 1) The present invention introduces a surfactant into the precursor aqueous solution to improve the surface adhesion of insoluble / hard-to-dissolve particles in the precursor aqueous solution during the grinding process, thereby achieving homogeneous mixing of the aqueous solution, and further drying, sintering and crushing to obtain the Na4Fe3(PO4)2P2O7 positive electrode material. The material has a uniformly distributed particle size, excellent powder compaction density, high crystal phase purity, and excellent electrochemical performance.
[0029] 2) The introduction of non-ionic surfactants also solves the problem of poor carbon coating effect during low-temperature carbonization of organic carbon sources such as glucose and sucrose in the traditional preparation process, and improves the carbon coating effect of composite sodium iron phosphate particles, which is mainly due to the surfactant improving the surface adhesion of iron phosphate particles. A good organic coating layer is formed in the primary granulation process, and the expansion of traditional carbon sources such as glucose during the carbonization process is suppressed. The carbon content of the iron-based phosphate positive electrode material can be regularly adjusted by adjusting the proportion of non-ionic surfactants.
[0030] 3) The sodium ion battery positive electrode sheet prepared from the iron-based phosphate positive electrode material prepared in the present invention has a high electrode sheet compaction density, and the gram capacity decay is low at a high compaction density. When applied to sodium ion batteries, the energy density of the battery can be further improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a SEM electron micrograph of the composite sodium iron phosphate positive electrode material obtained in Example 1 of the present invention;
[0032] Figure 2 The SEM electron micrograph of the composite sodium iron phosphate positive electrode material obtained in Comparative Example 1 of the present invention;
[0033] Figure 3 The X-ray diffraction curve (XRD) of the composite sodium iron phosphate positive electrode material obtained in Example 1 of the present invention;
[0034] Figure 4 The particle size distribution curve of the composite sodium iron phosphate positive electrode material is obtained for Example 1 of the present invention;
[0035] Figure 5 This is a charge and discharge curve diagram of an electrode sheet with a high compaction density obtained by obtaining a composite sodium iron phosphate positive electrode material in Example 1 of the present invention in a button half-cell;
[0036] Figure 6 This is a relationship diagram of the powder compaction density, pole piece compaction density and surfactant addition amount of the embodiments and comparative examples in the patent of the present invention. DETAILED DESCRIPTION
[0037] The specific preparation method of the present application is described below in conjunction with specific drawings so that those skilled in the art can better understand the present application.
[0038] Example 1: A method for preparing a sodium iron phosphate pyrophosphate positive electrode material and an electrode sheet thereof, comprising the following steps:
[0039] (1) Sodium hydrogen phosphate, sodium carbonate, sodium acetate, ferric phosphate, and ferrous oxalate are added to appropriate deionized water in a molar ratio of 2:0.5:1:2:1, and glucose is added as a carbon source. The mass ratio of the carbon source is controlled to be 8%, and the solid content of the solution is controlled to be 30%. The insoluble matter in the solution is dispersed using a ball mill.
[0040] (2) Grind the aqueous solution in step (1) to a slurry particle size of 0.2±0.05 μm, add 1% by mass of a surfactant fatty alcohol polyoxyethylene ether, and continue grinding and dispersing until there is no obvious precipitation in the slurry and the aqueous solution remains stationary for a long time without stratification, thereby obtaining a homogeneously mixed precursor aqueous solution.
[0041] (3) The precursor aqueous solution in step (2) is dried and granulated by a spray drying device, wherein the inlet air temperature of the spray drying is 180° C., the outlet air temperature is 95° C., and the drying atmosphere is air. After the spray drying is completed, the sodium iron pyrophosphate positive electrode material precursor can be obtained.
[0042] (4) The precursor material in step (3) is subjected to high-temperature heat treatment in a sintering furnace, wherein the heat treatment procedure is to increase the temperature to 250°C at a heating rate of 3°C / min and keep it at that temperature for 3 hours, then increase the temperature to 550°C at a heating rate of 2°C / min and keep it at that temperature for 10 hours. After cooling to room temperature, the sample is taken out to obtain the sodium iron pyrophosphate positive electrode material.
[0043] (5) The sodium iron phosphate pyrophosphate positive electrode material in step (4) is crushed and graded using a powder crushing device, and the final sodium iron phosphate pyrophosphate positive electrode material can be obtained after crushing and grading. The morphology of the material is as shown in the figure, showing a round spherical shape; the XRD curve of the material is as shown in Figure 2 As shown; the average particle size distribution of the material is 5±0.5μm, as Figure 3 As shown; the powder compaction density is 2.4g / cm 3 ; Carbon content is 1.7%.
[0044] The positive electrode material in step (5) is mixed with the conductive agent oily carbon nanotubes, Super P, and the binder polyvinylidene fluoride (PVDF) solution of N-methyl-2-pyrrolidone (NMP, mass fraction 5%) in a mass ratio of 9.3:0.2:0.1:0.4, and the slurry is coated on the aluminum foil. The aluminum foil is placed in a vacuum drying oven at 100°C for 10 hours to remove NMP, and then the dried aluminum foil is rolled and cut into electrode sheets with a diameter of 14 mm. The compacted density of the electrode sheet is 2.4 g / cm 3 .
[0045] The electrode sheet in step (7) was assembled into a button cell in a glove box with sodium metal as the counter electrode, 1 mol / L NaClO4EC / PC / DMC (volume ratio 1:1:1) as the electrolyte, PE as the separator, and CR2025 as the battery model. The above battery was subjected to constant current charge and discharge test with a current density of 25 mA / g. The test results are as follows: Figure 4 As shown, in the voltage range of 2.0 to 3.6 V, the reversible specific capacity is 111.5 mAh / g.
[0046] Example 2: Preparation method of sodium iron phosphate pyrophosphate positive electrode material, except that the surfactant in the aqueous solution accounts for 0.2%, and other conditions are the same as in Example 1. The results show that the sample powder compaction of this example is 2.0g / cm3, the pole piece compaction is 1.9g / cm3; the carbon content is 1.7%, and when assembled into a CR 2025 button battery, Figure 3 As shown, in the voltage range of 2.0 to 3.6 V, the reversible specific capacity is 98.14 mAh / g.
[0047] Example 3: Preparation method of sodium iron phosphate pyrophosphate positive electrode material, except that the surfactant in the aqueous solution accounts for 1.5%, and other conditions are the same as in Example 1. The results show that the sample powder of this example is compacted to 2.5g / cm3; the carbon content is 1.7%, and the pole piece is compacted to 2.4g / cm3. When assembled into a CR 2025 button battery, Figure 3 As shown, in the voltage range of 2.0 to 3.6 V, the reversible specific capacity is 106.8 mAh / g.
[0048] Example 4: Preparation method of sodium iron phosphate pyrophosphate positive electrode material, except that the surfactant in the aqueous solution accounts for 2%, and other conditions are the same as in Example 1. The results show that the sample powder of this example is compacted to 2.4g / cm3; the carbon content is 1.7%, and the pole piece is compacted to 2.3g / cm3. When assembled into a CR 2025 button battery, Figure 3 As shown, in the voltage range of 2.0 to 3.6 V, the reversible specific capacity is 102.7 mAh / g.
[0049] Example 5: Preparation method of sodium iron phosphate pyrophosphate positive electrode material, except that the surfactant in the aqueous solution accounts for 4%, other conditions are the same as in Example 1. The results show that the sample powder compaction of this example is 2.3g / cm 3 ; Carbon content is 1.7%, pole piece compaction is 2.2g / cm 3 , when assembled into a CR 2025 button battery, such as Figure 3 As shown, in the voltage range of 2.0 to 3.6 V, the reversible specific capacity is 99.8 mAh / g.
[0050] Example 6: Preparation method of sodium iron phosphate pyrophosphate positive electrode material, the surfactant type is replaced with alkylphenol polyoxyethylene ether, accounting for 1.5%, and other conditions are the same as Example 1. The results show that the sample powder compaction of this example is 2.15g / cm 3 ; Carbon content is 1.7%, pole piece compaction is 2.25g / cm 3 When assembled into a CR 2025 button battery, the reversible specific capacity is 99.5 mAh / g in the voltage range of 2.0 to 3.6 V.
[0051] Example 7: Preparation method of sodium iron phosphate pyrophosphate positive electrode material, the surfactant type is replaced with polyoxyethylene alkylphenol ether, accounting for 1.5%, and other conditions are the same as Example 1. The results show that the sample powder compaction of this example is 2.13g / cm 3 ; Carbon content is 1.7%, and the pole piece compaction is 2.23g / cm 3 When assembled into a CR 2025 button battery, the reversible specific capacity is 99.6 mAh / g in the voltage range of 2.0 to 3.6 V.
[0052] Example 8: Preparation method of sodium iron phosphate pyrophosphate positive electrode material, the surfactant type is changed to a mixture of fatty alcohol polyoxyethylene ether and alkylphenol polyoxyethylene ether, the mass ratio is 1:1, the slurry ratio is 1.5%, and other conditions are the same as Example 1. The results show that the sample powder compaction of this example is 2.1g / cm 3 ; Carbon content is 1.7%, pole piece compaction is 2.2g / cm 3 When assembled into CR 2025 button cells, the reversible specific capacity is 100.12 mAh / g in the voltage range of 2.0 to 3.6 V.
[0053] Example 9: Preparation method of sodium iron phosphate pyrophosphate positive electrode material, the surfactant type is changed to a mixture of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether and polyoxyethylene alkylphenol ether, the mass ratio is 1:1:1, the slurry ratio is 1.5%, and the other conditions are the same as Example 1. The results show that the sample powder compaction of this example is 2g / cm 3 ; Carbon content is 1.7%, pole piece compaction is 2.1g / cm 3 When assembled into a CR 2025 button battery, the reversible specific capacity is 100.31 mAh / g in the voltage range of 2.0 to 3.6 V.
[0054] Example 10: Preparation method of sodium iron phosphate pyrophosphate positive electrode material, except that the surfactant in the aqueous solution accounts for 0.2%, and other conditions are the same as in Example 1. The results show that the sample powder compaction of this example is 1.6g / cm 3, the pole piece compaction is 1.7g / cm 3 ; The carbon content is 1.7%. When assembled into a CR 2025 button battery, the reversible specific capacity is 93.14 mAh / g in the voltage range of 2.0 to 3.6 V.
[0055] Example 11: Preparation method of sodium iron phosphate pyrophosphate positive electrode material, except that the surfactant in the aqueous solution accounts for 4%, and other conditions are the same as in Example 1. The results show that the sample powder compaction of this example is 2.0g / cm 3 , the pole piece compaction is 2.1g / cm 3 ; The carbon content is 1.7%. When assembled into a CR 2025 button battery, the reversible specific capacity is 95.14 mAh / g in the voltage range of 2.0 to 3.6 V.
[0056] Comparative Example 1: Preparation method of sodium iron phosphate pyrophosphate positive electrode material, except that the aqueous solution does not have the addition of surfactant and the electrode compaction density is 1.7g / cm3; the carbon content is 1.7%, and other conditions are the same as in Example 1. The results show that the sample powder compaction density of this example is 1.8g / cm 3 , the pole piece compaction is 1.7g / cm 3 , when assembled into a CR 2025 button battery, such as Figure 3 As shown, in the voltage range of 2.0 to 3.6 V, the reversible specific capacity is 90 mAh / g. Table 1 Performance test results
[0057]
[0058] As can be seen from Table 1, the present invention introduces appropriate surfactants to regulate the mixing state of the precursor aqueous solution, thereby obtaining a homogeneous state of the aqueous solution during the grinding process. The positive electrode material obtained by further drying and high-temperature heat treatment has excellent electrode compaction density and excellent gram capacity at the compaction density.
[0059] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, it should be understood by those skilled in the art that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
[0060] The above description is only a preferred feasible implementation example of the present invention, and does not limit the scope of rights of the present invention. All equivalent structural changes made using the contents of the present invention and the drawings are included in the scope of rights of the present invention.
Claims
1. A method for preparing a composite sodium iron phosphate positive electrode material with a high compaction density, characterized in that: The following steps are involved: (1) The sodium source, iron source, phosphorus source, etc. for preparing the composite sodium iron phosphate positive electrode material are measured, mixed and ground according to the chemical formula Na4Fe3(PO4)2P2O7, and a carbon source with a mass percentage of 8% is added to obtain a precursor aqueous solution; (2) adding a surfactant to the precursor aqueous solution, grinding and mixing the mixture to obtain a homogeneous precursor aqueous solution; (3) drying and granulating the homogeneous precursor aqueous solution by spray drying technology to obtain composite sodium iron phosphate precursor particles; (4) subjecting the composite sodium iron phosphate precursor particles to high-temperature heat treatment under the protection of an inert gas to obtain a composite sodium iron phosphate positive electrode material.
2. The method for preparing a composite sodium iron phosphate positive electrode material according to claim 1, characterized in that: The mixing ratio of the sodium source, the iron source and the phosphorus source is 4:3:
4.
3. The method for preparing a composite sodium iron phosphate positive electrode material according to claim 1, characterized in that: The sodium source includes one or more of sodium acetate, sodium oxalate, sodium nitrate, sodium citrate, sodium phosphate, and sodium alginate; The iron source includes one or more of ferric phosphate, ferrous oxalate, ferric nitrate and ferric sulfate; The phosphorus source includes one or more of sodium dihydrogen phosphate, disodium hydrogen phosphate, phosphoric acid, diammonium dihydrogen phosphate, triammonium phosphate, diammonium hydrogen phosphate, sodium phosphate, etc.; The carbon source includes one or more of citric acid, glucose, sucrose, polyethylene glycol, lignin, nanocellulose, and phenolic resin.
4. The method for preparing a composite sodium iron phosphate positive electrode material according to claim 1, characterized in that: The surfactant includes one or more of fatty alcohol polyoxyethylene ether (A), alkylphenol polyoxyethylene ether (B) and polyoxyethylene alkylphenol ether (C).
5. The method for preparing a composite sodium iron phosphate positive electrode material according to claim 4, characterized in that: After the surfactant is introduced, its mass proportion in the precursor aqueous solution is 0.2-4%.
6. The method for preparing a composite sodium iron phosphate positive electrode material according to claim 1, characterized in that: The average particle size of the homogeneous precursor aqueous solution is 0.1 μm to 0.7 μm, and the solid content of the homogeneous precursor aqueous solution is 15% to 60%.
7. The method for preparing a composite sodium iron phosphate positive electrode material according to claim 1, characterized in that: In the step (3), the spray drying technology, wherein the drying temperature is 170°C to 250°C, and the drying atmosphere is one of air, nitrogen, and argon; In step (4), the high temperature heat treatment temperature is 400°C to 600°C, the heat treatment time is 3 to 10 hours, the inert gas is one of nitrogen or argon, and the heating rate is 1°C / min to 10°C / min.
8. The method for preparing a composite sodium iron phosphate positive electrode material according to claim 1, characterized in that: The average particle size of the composite sodium iron phosphate positive electrode material is 300-700 nm; the carbon content is 1.5-2.0%; and the powder compaction density is 2.0-2.65 g / cm 3 .
9. A composite sodium iron phosphate positive electrode material, characterized in that: The composite sodium iron phosphate positive electrode material is prepared by the preparation method of the composite sodium iron phosphate positive electrode material according to claims 1 to 8.
10. A positive electrode sheet for a sodium ion battery, characterized in that: It is prepared from the composite sodium iron phosphate positive electrode material according to claim 9.
11. The sodium ion battery positive electrode sheet according to claim 10, characterized in that: The compaction density of the sodium ion battery positive electrode sheet is 1.5 g / cm 3 ~2.4g / cm 3 .
12. A sodium ion battery, characterized in that: Use the sodium ion battery positive electrode sheet according to claims 10 to 11.
Citation Information
Patent Citations
Preparation method of metal-based phosphate positive electrode material of sodium-ion battery
CN116621148A
High-stability composite sodium ferric phosphate positive electrode material and preparation method thereof
CN118738314A
Cited By
Sodium ferric pyrophosphate positive electrode material for sodium ion battery and preparation method of sodium ferric pyrophosphate positive electrode material
CN120589713A
Fluorine-doped ferric sodium pyrophosphate positive electrode material as well as preparation method and application thereof
CN120841474A
Preparation method of high-compaction-density composite sodium ferric phosphate positive electrode material
CN120864468A
Preparation method of high-compaction-density composite sodium iron phosphate positive electrode material
CN120864468B